2017
DOI: 10.5693/djo.01.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on the outcomes of Ahmed valve versus Ahmed valve combined with fluocinolone implant in uveitic glaucoma

Abstract: Purpose-To compare the intraocular pressure (IOP) outcomes of Ahmed glaucoma valve (AGV) surgery alone versus AGV with fluocinolone implant in uveitic glaucoma patients.Methods-We identified uveitic glaucoma patients with AGV surgery alone and AGV surgery combined with fluocinolone implant from the Massachusetts Eye and Ear Ocular Inflammation Database. Demographic information, visual acuity, and IOP were recorded at preoperative visits and 1, 6, and 12 months after surgery. Incidence of hypertensive phase, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…Prior studies have reported similar outcomes from the combined placement of a sustained-release fluocinolone acetonide intravitreal implant with glaucoma drainage device among patients with uveitic glaucoma. 9,[11][12][13][14][15][16] These results were consistent among a variety studies that included patients with single-session combined surgery (with or without concurrent cataract extraction) and/or consecutive glaucoma drainage device placement following fluocinolone acetonide intravitreal implantation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Prior studies have reported similar outcomes from the combined placement of a sustained-release fluocinolone acetonide intravitreal implant with glaucoma drainage device among patients with uveitic glaucoma. 9,[11][12][13][14][15][16] These results were consistent among a variety studies that included patients with single-session combined surgery (with or without concurrent cataract extraction) and/or consecutive glaucoma drainage device placement following fluocinolone acetonide intravitreal implantation.…”
Section: Discussionsupporting
confidence: 74%
“…Their study found 2 eyes that underwent reoperation, including one within the first 30 days following surgery for tube repositioning. 11 Sevgi et al 16 also noted 2 tube erosions in the same patient among 7 eyes that underwent combined surgery. Moore et al 11 reported adverse events in 2 of 22 eyes, including 1 eye that lost light perception vision, and 1 eye that required an additional IOP-lowering procedure.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…9 Sevgi et al found the presence of inflammation did not change significantly in the Ahmad Glaucoma Valve (AGV), the only group compared to the AGV+ fluocinolone implant group. 10 In line with Sevgi et al, Zivney et al found fluocinolone implant had better control intraocular inflammation. 10,11 Figure 3 showed the number of glaucoma medications was decreased postoperatively in all studies on average Generally, common complications were hypotony, choroidal effusion, hyphema, shallow anterior chamber, blocked tube, and corneal edema.…”
Section: Reviewmentioning
confidence: 73%
“…A AV corrigida com notação em Snellen foi convertida no logaritmo do ângulo mínimo de resolução (logarithm of the Minimum Angle of Resolution, logMAR). Para um AV inferior a 20/400, as equivalências em logMAR foram as seguintes: contagem de dedos (CD) = 1,98; movimentos da mão (MM) = 2,28; percepção luminosa (PL) = 2,80 72,73 . O registro de sem percepção luminosa (SPL) foi convertido a um valor de 2,9 74 .…”
Section: Medidas Da Acuidade Visualunclassified